Damage Probability Matrices for Three-Nave Masonry Churches in Abruzzi After the 2009 L'Aquila Earthquake. Issue 2 (2nd April 2016) - De Matteis, Gianfranco; Criber, Emanuela; Brando, Giuseppe
ABSTRACT: This article provides the main outcomes obtained downstream from a survey concerning the damage to 64 three-nave masonry churches in Abruzzi resulting from the 2009 L'Aquila earthquake. First, they are classified according to the typological, structural, and architectural features. Next, the main failure mechanisms observed in the immediate aftermath of the 2009 earthquake are identified and analyzed, taking into account both the global structural response and the local mechanisms involving specific parts of the churches. Damage related to the local mechanisms is classified by means of scores based on both the severity and extension of the revealed cracks. The single scores are combined to define an index measuring the global damage of each church. Such indices are therefore associated with six damage levels, the frequencies of which are organized into damage probability matrices. These matrices can be used in order to quantitatively evaluate the damage scenarios that the studied population of buildings revealed after the seismic event, as well as to predict the damage level that could be expected on similar churches for future earthquakes.